Reutilização de lodo de esgoto para produção de catalisadores e aplicação no processo Fenton heterogêneo - Costa Neto, Daniel Salustiano (2020)
Carbonaceous materials can be prepared from biomass by hydrothermal carbonization and used as catalysts in the degradation of dyes in wastewater by Fenton reactions. Here we report on the synthesis of catalysts by hydrothermal carbonization of sewage sludge and its application in tartrazine degradation. Two series of catalysts were prepared from the sewage sludge with different dewatering periods, L2 and L8. The performances of the L8 series materials were better than those of the L2 series, with emphasis on the catalysts SAC8A−Fe produced in smaller particle size and SAC8B−Fe2, produced under conditions of greater pressure in the hydrothermal carbonization process. The material was characterized by physical-chemical analyses, thermal analyses (TG/DTG), chemical analysis (EDX), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) and adsorption studies and degradation by the Fenton reaction. The conversion rate of SAC8A−Fe and SAC8B−Fe2 was 40% in 50 minutes while the other materials reached this level in 120 minutes. The results obtained can contribute to new synthesis conditions for catalysts and increase the possibilities in the generation of products with a higher added value from sewage sludge.